The Kat in the HAT: The Histone Acetyl Transferase Kat6b (MYST4) Is Downregulated in Murine Macrophages in Response to LPS - Smita Shukla; Carly Levine; Roopa Payanur Sripathi; Genie Elson; Carol Susan Lutz; Samuel Joseph Leibovich (Mediators of Inflammation)
Epigenetic modulators, including histone methylases, demethylases, and deacetylases, have been implicated previously in the regulation of classical and alternative macrophage activation pathways. In this study, we show that the histone acetyl transferase (HAT) Kat6B (MYST4) is strongly suppressed (>80%) in macrophages by lipopolysaccharide (LPS) (M1 activation), while Kat6A, its partner in the MOZ/MORF complex, is reciprocally upregulated. This pattern of expression is not altered by LPS together with the adenosine receptor agonist NECA (M2d activation). This is despite the observation that miR-487b, a putative regulator of Kat6B expression, is mildly stimulated by LPS, but strongly suppressed by LPS/NECA. Other members of the MYST family of HATs (Kat5, Kat7, and Kat8) are unaffected by LPS treatment. Using the pLightswitch 3′UTR reporter plasmid, the miR-487b binding site in the Kat6b 3′UTR was found to play a role in the LPS-mediated suppression of Kat6B expression, but other as-yet unidentified factors are also involved. As Kat6B is a HAT that has the potential to modulate gene expression by its effects on chromatin accessibility, we are continuing our studies into the potential roles of this epigenetic modulator in macrophage activation pathways.